Plasma Endoglin is Associated with Favorable Outcome for Pemetrexed-Based Therapy in Advanced Non-Small Cell Lung Cancer - Li CH; Ko JL; Hsiao YP; Tsai MH; Lai YC; Hsin IL; Kang YT; Sheu GT; Lin WL; Wu MF (Cancer Management and Research, 2021)
Che-Hsing Li,1,2,* Jiunn-Liang Ko,1,3,4,* Yu-Ping Hsiao,5,6 Ming-Hung Tsai,7 Yen-Chein Lai,8 I-Lun Hsin,3,4 Yu-Ting Kang,3,4 Gwo-Tarng Sheu,1,3,4 Wea-Lung Lin,6,9 Ming-Fang Wu1,4,6 1Divisions of Medical Oncology and Pulmonary Medicine, Department of Internal Medicine, Chung Shan Medical University Hospital, Taichung, 402, Taiwan; 2Graduate Program in Immunology & Microbiology, Baylor College of Medicine, Houston, TX, 77030, USA; 3Institute of Medicine, Chung Shan Medical University, Taichung, 402, Taiwan; 4CSMU Lung Cancer Research Center, Chung Shan Medical University, Taichung, 402, Taiwan; 5Division of Dermatology, Chung Shan Medical University Hospital, Taichung, 402, Taiwan; 6School of Medicine, Chung Shan Medical University, Taichung, 402, Taiwan; 7Division of Hematology and Oncology, Department of Internal Medicine, China Medical University Hospital, Taichung, 40447, Taiwan; 8Department of Medical Laboratory and Biotechnology, Chung Shan Medical University, Taichung, 402, Taiwan; 9Department of Pathology, Chung Shan Medical University Hospital, Taichung, 402, Taiwan*These authors contributed equally to this workCorrespondence: Ming-Fang WuDivisions of Medical Oncology and Pulmonary Medicine, Department of Internal Medicine, Chung Shan Medical University Hospital, 110, Sec. 1, Jianguo N. Road, Taichung, 40201, TaiwanTel +886-4-24739595#34711Email mfwu0111@gmail.comPurpose: Pemetrexed-based chemotherapy (Pem-C) is the first-line chemotherapy for advanced non-squamous non-small cell lung cancer (NSCLC). However, limited tumor-associated proteins in blood are available to predict pemetrexed response and/or survival.Patients and Methods: Plasma samples from three responders and three nonresponders with stage IIIB–IV NSCLC were collected prior to Pem-C and analyzed using Proteome ProfilerTM Human XL Oncology Array to detect 84 oncology-related proteins. The plasma concentrations of cathepsin S, endoglin (ENG), and matrix metalloproteinases 3 and 9 in 71 patients with advanced NSCLC treated with Pem-C were further measured using enzyme-linked immunosorbent assay based on the remarkable differences in the four proteins between responders and nonresponders in the array results.Results: Pem-C responders had significantly higher ENG levels but not the other three markers than nonresponders (mean ENG level: 27.1 ± 7.4 vs 22.3 ± 6.9, p < 0.01). High ENG concentration was correlated with improved progression-free survival (hazard ratio [HR]: 0.52, 95% confidence interval [CI]: 0.31– 0.86, p < 0.01) and overall survival (HR: 0.55, 95% CI: 0.32– 0.94, p < 0.05) in patients treated with Pem-C, and the ENG level was an independent factor in our cohort (HR: 0.54, 95% CI: 0.33– 0.89, p < 0.05). ENG concentration in Pem-C responders also significantly increased at the time of best response (p < 0.05).Conclusion: Cumulatively, this study reveals that ENG is correlated with Pem-C responsiveness in patients, which indicates the potential use of plasma ENG levels as a non-invasive biomarker for pemetrexed-based treatment in patients with non-squamous NSCLC.Keywords: endoglin, pemetrexed-based therapy, prognostic factor, non-squamous non-small cell lung cancer, biomarker